2003
DOI: 10.1097/01.sap.0000041487.47731.d0
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Vasculature of the Forearm

Abstract: Five fresh human cadavers were injected with lead oxide, gelatin, and water. Nine forearms were dissected and an overall map of the cutaneous vasculature by source vessel was constructed. The average number of arterial perforators per source vessel was calculated. The forearm was then divided into three regions, and the density of perforators per region was calculated and compared. The overall number of arterial perforators decreases from proximal to distal in the forearm, but the overall density of perforator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…More, the use of such flaps as the most recently described perforator flaps seems to represent a major advantage, especially because they avoid the sacrifice of a main artery. 49 The use of this type of flaps in the forearm became possible and broadened their application area after some comprehensive experimental studies regarding the skin vascular pattern in the upper limb 11,29,[31][32][33]34,36 and the study of angiosomes. 28,30,31,45 The harvesting of this kind of flaps needs a very minute dissection, better under magnification, but does not need microvascular sutures; that is why we named these flaps microsurgical nonmicrovascular flaps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More, the use of such flaps as the most recently described perforator flaps seems to represent a major advantage, especially because they avoid the sacrifice of a main artery. 49 The use of this type of flaps in the forearm became possible and broadened their application area after some comprehensive experimental studies regarding the skin vascular pattern in the upper limb 11,29,[31][32][33]34,36 and the study of angiosomes. 28,30,31,45 The harvesting of this kind of flaps needs a very minute dissection, better under magnification, but does not need microvascular sutures; that is why we named these flaps microsurgical nonmicrovascular flaps.…”
Section: Discussionmentioning
confidence: 99%
“…32,36 The anterior interosseous artery (AIOA) 28,30,37,38 blood supplies the skin over the lateral border of the forearm (over the lower part of extensor pollicis brevis and abductor pollicis longus) through three perforating branches, the most important of them being one that emerges at the proximal border of the pronator quadratus muscle and supplies the extensor muscles of the thumb and the skin over the distal 2/3 of the dorsal aspect of the forearm. 39 The posterior interosseous artery (PIOA) 28,30,36,40,41 gives two groups of fasciocutaneous perforators ( Fig. 5): (1) the first group in the proximal part, which blood supplies the skin between flexor carpi ulnaris and extensor carpi ulnaris muscles; (2) the second group is given off in the lower 2/3, between extensor carpi ulnaris and extensor digiti minimi proprius; their branches fan out in all directions.…”
Section: Anatomical Considerationsmentioning
confidence: 99%
“…Past studies have identified that the diameter of perforating vessels decreases as the radial artery diminishes in calibre. 11,24 The average diameter and length from origin both decreased with distal location in this study. These results demonstrate that there are many small, short perforators supplying the skin where the distal skin paddle extension is planned according to this suggested modification.…”
Section: Discussionmentioning
confidence: 71%
“…The discrepancy between BF and THb is interpreted as the different BF velocities among these sites, with a higher velocity at the fingertip than in other areas. Such high velocities are thought to reflect the presence of more arterial vessels in the fingertip than in the forearm (Kanellakos et al, 2003). Accordingly, BF velocity was higher at the fingertip than in the other areas.…”
Section: Discussionmentioning
confidence: 94%
“…The high BF and StO 2 levels at fingertip can be explained anatomically. There are more integrated arterial blood vessels that contain abundant OxyHb in the fingertip than in the forearm (Kanellakos et al, 2003). In addition, the dense distribution of AVAs in fingertip skin may be involved in the high StO 2 levels.…”
Section: Discussionmentioning
confidence: 99%